Cardiac Angiosarcoma - Monique Esteves Cardoso; Leonardo Secchin Canale; Rosana Grandelle Ramos; Edson da Silva Salvador Junior; Stephan Lachtermacher (Case Reports in Cardiology)
Despite cardiac metastases are found in about 20% of cancer deaths, the presence of primary cardiac tumors is rare. Most primary tumors are benign, and malignant tumors comprise about 15%. We report a 21-year-old man with fever, dyspnea, and hemoptysis that was diagnosed with angiosarcoma of the right atrium and pulmonary metastasis. Patient was submitted to surgical tumor resection without adjuvant therapy and died four months after diagnosis.